(untitled) (Research, Society and Development, 2021)
Introduction: Individuals living with HIV can be affected by discrimination and fear due to the impact of the diagnosis of a chronic infection with no cure. In addition, they can develop neurological diseases due to direct organ damage or cognitive changes associated with HIV, depression being a problem that can be common in this public. Objective: To assess the presence and intensity of depressive symptoms in men and women living with HIV. Method: Cross-sectional study with a quantitative approach carried out with 76 people diagnosed with HIV and registered in a specialized clinic. The Beck Depression Inventory (BDI) was used as an instrument for data collection. The comparison analysis between the male and female genders was performed using Fisher’s exact test and Man Withney’s test using the Biostat 5.3 Software. Results: Men aged 20 to 39 years presented depressive symptoms in moderate to severe levels (50%) and 45.2% of women had severe depression (p = 0.002). Women had higher mean scores of depressive symptoms than men, both in the affective-cognitive domain (p = <0.05) and in the somatic domain (p = <0.05). Conclusion: Women have higher scores of depressive symptoms in the affective-cognitive and somatic domains in the BDI. It is important that health professionals understand and identify depressive symptoms and their severity in their clinical practice, as they can manifest themselves under different intensities between men and women.